Weather and climate around the world - Machajewski, Sarah (Spotlight on weather and natural disasters., 2019)
Describes the differences between weather and climate and highlights notable natural phenomena that are impacted by both, such as flash floods, drought, and blizzards. Includes color photographs, a glossary, and online resources.